2023
DOI: 10.1007/s11356-023-27317-2
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence against healthcare workers during the COVID-19 pandemic: a systematic review and meta-analysis

Abstract: Workplace violence (WPV) is a prevalent phenomenon, especially in the healthcare setting. WPV against healthcare workers (HCWs) has increased during the COVID-19 epidemic. This meta-analysis determined the prevalence and risk factors of WPV. A database search was conducted across six databases in May 2022, which was updated in October 2022. WPV prevalence among HCWs was the main outcome. Data were stratified by WPV/HCW type, pandemic period (early, mid, late), and medical specialty. WPV risk factors were the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 71 publications
1
10
0
1
Order By: Relevance
“…In contrast, violence could be a consequence of stigmatization and negative public attitudes that develop over time and manifest later as frustration increases. Although the occurrence of workplace violence among Czech HCWs is lower than that reported in a previous meta-analysis 39 , the trend in the data is the same. This tendency could be explained by an increased number of patients and their long-term stress and dissatisfaction caused by the pandemic and by an urge to direct frustration toward HCWs 40 .…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…In contrast, violence could be a consequence of stigmatization and negative public attitudes that develop over time and manifest later as frustration increases. Although the occurrence of workplace violence among Czech HCWs is lower than that reported in a previous meta-analysis 39 , the trend in the data is the same. This tendency could be explained by an increased number of patients and their long-term stress and dissatisfaction caused by the pandemic and by an urge to direct frustration toward HCWs 40 .…”
Section: Discussionsupporting
confidence: 41%
“…All employees in health care should be provided with supervision and psychological help. Workplaces should also implement anti-violence strategies and violence prevention training 39 . The reduction of negative social aspects of the job in health care, such as a lack of support from management, psychological stress, excessive demands, long-term shortages of personnel, and job insecurity, should also be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with Chinese psychiatrists revealed that doctors who experience workplace violence exhibit greater intentions to leave their current position than do those who do not [32]. The incidence of workplace violence targeting healthcare professionals has surged during the COVID-19 pandemic [33,34]. Factors such as fear of the novel coronavirus [35] and inadequate personnel and resources available to meet patient demands[36] may signi cantly contribute to this escalation.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Previous studies conducted in China have been limited in terms of study sites and sample sizes, which may have impacted the validity of their findings. Moreover, these studies often failed to report the prevalence rates and associated factors in different units 21–23 . Psychiatrists, in particular, are more susceptible to higher levels of SH compared to those working in other medical specialties.…”
Section: Introductionmentioning
confidence: 99%